Kenya's Colony Music and Drama Officer - Hyslop, Graham H. (International Library of African Music, 1958)
The Department of Community Development in Kenya realised long ago that a constructive and imaginative use of leisure can do much to fill the vacuum left by the abandonment in many instances of traditional forms of entertainment in Africa. The increasing interest in Music and Drama in the territory during recent years, particularly amongst the African population, seemed to call for a re-assessment of the role of the Department in these spheres of adult life. At Jeanes School, the Colony’s main centre for general adult education, it had been possible to make some contribution in this field already. Most of this however had had to be made during the vacations and it became clear that it would be detrimental to other work at Jeanes School even to attempt to maintain the contribution, and quite out of the question to contemplate increasing the assistance which could be given. There was an ever-increasing number of requests for help being made, and in order to meet this demand, it was decided early in 1957 to release a member of staff at Jeanes School from general duties in order that he might take up responsibilities as Colony Music and Drama Officer.
Keywords: Music; Music festivals; Choirs (Music); Choral conductors; Ethnomusicology; Festivals; Education; Kenya; African Music